Pengaruh Variasi Pukulan terhadap Kekerasan Baja menggunakan Mesin Hammer Otomatis - Kiki Qauri Valentino; M. Rasid; Dwi Arnoldi (Jurnal Serambi Engineering, 2025)
This study evaluates the effect of varying hammer strokes during the forging process using an automatic hammer machine on the hardness of ST 37 steel, ST 60 steel and automotive leaf springs. The experiments were carried out at a temperature of 600°C to analyse dimensional changes and material hardness resulting from plastic deformation. Data was obtained from thickness and hardness tests using the Vickers method. Variations in hammer strokes (0, 32 and 49 strokes) resulted in a significant increase in material hardness. For ST 37 steel the hardness increased from 137,964 kgf/mm² to 170,088 kgf/mm², for ST 60 steel from 158,781 kgf/mm² to 172,56 kgf/mm² and for automotive leaf springs from 198,442 kgf/mm² to 241,756 kgf/mm². This improvement is attributed to the strain hardening mechanism, which induces the accumulation of dislocations in the microstructure of the material, thereby increasing its resistance to further deformation. The variation in hammer strokes also influenced the changes in material thickness, with different levels of deformation depending on the mechanical properties of each material. ST 60 steel showed a more controlled deformation response compared to ST 37 steel, while automotive leaf springs showed greater deformation due to their more ductile nature. These results emphasise that forging process parameters, such as the number of hammer strokes, play a crucial role in enhancing the mechanical properties of materials to meet specific engineering application requirements.